Epithelial‐mesenchymal transition is activated in CD44‐positive malignant ascites tumor cells of gastrointestinal cancer. Issue 11 (27th September 2018) - Nakano, Michitaka; Ito, Mamoru; Tanaka, Risa; Ariyama, Hiroshi; Mitsugi, Kenji; Makiyama, Akitaka; Uchino, Keita; Esaki, Taito; Tsuruta, Nobuhiro; Hanamura, Fumiyasu; Yamaguchi, Kyoko; Okumura, Yuta; et al.
Abstract : Disseminated cancer cells in malignant ascites possess unique properties that differ from primary tumors. However, the biological features of ascites tumor cells (ATC) have not been fully investigated. By analyzing ascites fluid from 65 gastrointestinal cancer patients, the distinguishing characteristics of ATC were identified. High frequency of CD44 + cells was observed in ATC using flow cytometry (n = 48). Multiplex quantitative PCR (n = 15) showed higher gene expression of epithelial‐mesenchymal transition (EMT)‐related genes and transforming growth factor beta (TGF‐beta)‐related genes in ATC than in the primary tissues. Immunohistochemistry (n = 10) showed that ATC also had much higher expression of phosphorylated SMAD2 than that in the corresponding primary tissues. TGF‐beta 1 was detected in all cases of malignant ascites by enzyme‐linked immunoassay (n = 38), suggesting the possible interaction of ATC and the ascites microenvironment. In vitro experiments revealed that these ATC properties were maintained by TGF‐beta 1 in cultured ATC(n = 3). Here, we showed that ATCrevealed high frequencies of CD44 and possessed distinct EMT features from primary tissues that were mainly maintained by TGF‐beta 1 in the ascites. Abstract : The overwhelming high frequency of CD44 in ascites tumor cells is observed. The epithelial‐mesenchymal transition phenotype of ascites tumor cells is maintained by TGF‐beta signaling from the ascites microenvironment.